Sorption and biodegradation of six pharmaceutically active compounds under four different redox conditions. (February 2018) - de Wilt, Arnoud; He, Yujie; Sutton, Nora; Langenhoff, Alette; Rijnaarts, Huub
Abstract: This study explored the removal of six pharmaceutically active compounds (PhACs) in lab-scale experiments with sediments under four redox conditions, namely aerobic, nitrate reducing, sulfate reducing, and methanogenic conditions using batch and column set-ups. Redox conditions were found to influence PhAC removal by sorption and biodegradation. The most optimal PhAC removal was observed at the outer ranges of the redox spectrum, i.e. either aerobic or deep anaerobic (sulfate reducing and methanogenic conditions), whereas nitrate reducing conditions were found least effective for PhACs biodegradation and sorption. For instance, sorption coefficient Kd values for metoprolol in column experiments were 90, 65, 42 and 11 L/kg for sulfate reducing, methanogenic, aerobic and nitrate reducing conditions, respectively. For the same conditions Kd values for propranolol were 101, 94, 55 and 55 L/kg, respectively. As expected, biodegradation efficiencies were highest under aerobic conditions, showing >99% removal of caffeine and naproxen, but no removal for propranolol and carbamazepine. The adaptive capacity of sediment was demonstrated by pre-exposure to PhACs leading to improved PhAC biodegradation. The results of this study indicate the necessity to combine diverse redox conditions, including aerobic conditions, for maximizing PhAC removal by sorption and biodegradation. Furthermore, our findings stress the need for additional treatment measures as recalcitrant PhACs are not effectively removed under any redox condition. Graphical abstract: Image 1 Highlights: Redox conditions influence sorption and biodegradation of PhACs. Lowest sorption of PhACs was found under nitrate reducing conditions. Caffeine effectively biodegraded under all tested redox conditions. Enrichment of biomass accelerates biodegradation of PhACs.